Preventive and therapeutic effect of Lactobacillus paracasei ZFM54 on Helicobacter pylori-induced gastritis by ameliorating inflammation and restoring gastric microbiota in mice model - Zhou, Qingqing; Qureshi, Nuzhat; Xue, Bingyao; Xie, Zuorui; Li, Ping; Gu, Qing (Frontiers in Nutrition, 2022)
Helicobacter pylori is the most prevalent pathogen causing chronic gastritis, gastroduodenal ulcers and gastric tumors, and asymptomatically present in 50% of the world’s population. This research is focused on investigating the effect of Lactobacillus paracasei ZFM 54 (CCTCC NO:2016667) on attenuating H. pylori-induced gastritis. H. pylori ZJC03 isolated from gastritis patient harbored the virulence genes of vacA and cagA, and was highly resistant to metronidazole (MIC > 256 μg/mL). In vitro analysis revealed that the potential anti-H. pylori characteristics of L. paracasei ZFM54 in terms of 65.57 ± 1.87% survival rate in simulated gastric juices at pH 2.0, 69.00 ± 2.73% auto-aggregation, 30.28 ± 2.24% co-aggregation, 70.27 ± 2.23% urease inhibition and 57.89 ± 1.27% radical scavenging. In H. pylori infectious mice, L. paracasei ZFM54 pre- and post-treatment reduced the levels of malondialdehyde in liver tissues were reduced to 0.71 ± 0.04 nmol/mgprot (p < 0.05) and 0.70 ± 0.06 nmol/mgprot (p < 0.05), respectively. Glutathione levels were increased to 1.78 ± 0.02 μmol/gprot (p < 0.05) and 1.76 ± 0.52 μmol/gprot (p < 0.05), respectively. L. paracasei ZFM54 significantly inhibited H. pylori-mediated inflammation observed in gastric mucosal repair and down-regulated mRNA expression of pro-inflammatory cytokines IFN-γ, IL-1β and IL-6 (p < 0.01). Importantly, L. paracasei ZFM54 increased Firmicutes and Actinobacteriota, and decreased the relative abundance of bacterial taxa belonging to Campilobacterota and Proteobacteria. With the preventive and therapeutic administration of L. paracasei ZFM54, significant reductions in the average relative abundance of genera Helicobacter, Muribaculum, Staphylococcus, Lachnospiraceae_NK4A136_group, Prevotellaceae_UCG-001, Alloprevotella and Oscillibacter were observed compared to infected mice. These findings suggest that L. paracasei ZFM 54 has the potential to protect against H. pylori infection by ameliorating inflammation and restoring the gastric microbiota.